2014
DOI: 10.1007/s11605-014-2601-6
|View full text |Cite
|
Sign up to set email alerts
|

Low Drain Fluid Amylase Predicts Absence of Pancreatic Fistula Following Pancreatectomy

Abstract: Introduction Improvements in the ability to predict pancreatic fistula could enhance patient outcomes. Previous studies demonstrate that drain fluid amylase on postoperative day 1 (DFA1) is predictive of pancreatic fistula. We sought to assess the accuracy of DFA1 and to identify a reliable DFA1 threshold under which pancreatic fistula is ruled out. Methods Patients undergoing pancreatic resection from November 1, 2011 to December 31, 2012 were selected from the American College of Surgeons-National Surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 22 publications
3
60
0
Order By: Relevance
“…21 Further details regarding the PDP have previously been published. [22][23][24][25][26] Study patients During the study period, 2805 patients underwent a pancreatic resection at the 43 participating institutions. Patients who underwent total pancreatectomy, distal pancreatectomy, enucleation, and minimally invasive PD were excluded.…”
Section: Pancreatectomy Demonstration Projectmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Further details regarding the PDP have previously been published. [22][23][24][25][26] Study patients During the study period, 2805 patients underwent a pancreatic resection at the 43 participating institutions. Patients who underwent total pancreatectomy, distal pancreatectomy, enucleation, and minimally invasive PD were excluded.…”
Section: Pancreatectomy Demonstration Projectmentioning
confidence: 99%
“…The primary outcomes of this study were perioperative overall morbidity, serious morbidity as previously defined, [22][23][24][25][26] mortality, and POPF-associated mortality. Aside from the variables collected by general participation in ACS-NSQIP, the 43 institutions participating in the PDP recorded 24 additional pancreatectomyspecific variables.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…4,7,[17][18][19][20][21][22][23][24][25][26][27][28][29] The process of selecting trials for inclusion is shown in Figure 1. The characteristics of these 15 studies are shown in Table 1.…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The Fagan plot in DPA1 for overall POPF [17][18][19][20][21][22][24][25][26][27][28][29] calculated that the positive post-test probabilities (post-test (ĂŸ)) were 0.57, 0.80, 0.92 respectively, and the negative posttest probabilities (post-test (À)) were 0.04, 0.10, 0.25 respectively when the pretest probability was 25% or 50% or 75%. For PPA1 [22,[27][28][29], the post-tests (ĂŸ) were 0.39, 0.66, 0.85 respectively, and the post-tests (À) were 0.12, 0.30, 0.56 respectively.…”
Section: Fagan Plot Analysismentioning
confidence: 99%
“…The ACS-NSQIP Pancreatectomy Demonstration Project, for instance, seeks to provide a multitude of HPB-specific variables (preoperative biliary stent placement, pancreatic duct diameter and remnant gland texture, anastomotic technique and vascular resection, drain placement and amylase levels, rates of PF, and delayed gastric emptying (DGE)) so that outcomes researchers can address very precise questions on a much broader scale. [21][22][23] As an example, this pilot database has been utilized by Parmar et al 24 to identify PF formation, postoperative sepsis and reoperation as independent predictors of DGE following PD or total pancreatectomy. Similarly, multicenter consortiums are primed tools for investigating questions related to subspecialty-specific surgical outcomes and harbor the added benefit of promoting widespread collaboration and idea sharing among various facilities.…”
mentioning
confidence: 99%